1969
DOI: 10.1002/aja.1001250105
|View full text |Cite
|
Sign up to set email alerts
|

Origin and early migration of primordial germ cells in the chick embryo: A study of the stages definitive primitive streak through eight somites

Abstract: The germinal crescent in the chirk embryo is characterized by small, PAS-positive, nonglycogen granules from 1.5 to 5 4 in diameter. The primordial germ rells (PGCs) were found to originate in and separate from the germinal crescent endoderm through stage 7 (2 somites). Shortly after separation most of the granules in the PGCs lost their organization and the PAS-positive material was distributed irregularly throughout the cytoplasm. A few of these granules remained within the cells indefinitely. Glycogen of an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 12 publications
3
14
0
Order By: Relevance
“…It was recently demonstrated that the binding-specificity of GS-I1 is not only N-acetylglucosamine residues but also glycogen in situ (Hennigar et al, 19861. As described in Results, cytoplasmic binding sites for GS-I1 in chick PGC appeared to be glycogen granules because of the inhibition test. Actually, this binding pattern was similar to the distribution of PAS-positive glycogen granules in the PGC (Clawson and Domm, 1969;Fujimoto et al, 1976). Different from the chick, quail PGC did not show GS-I1 reaction at any stages examined, indicating that no glycogen granules were Dresent in the germ cells.…”
Section: Discussionsupporting
confidence: 70%
“…It was recently demonstrated that the binding-specificity of GS-I1 is not only N-acetylglucosamine residues but also glycogen in situ (Hennigar et al, 19861. As described in Results, cytoplasmic binding sites for GS-I1 in chick PGC appeared to be glycogen granules because of the inhibition test. Actually, this binding pattern was similar to the distribution of PAS-positive glycogen granules in the PGC (Clawson and Domm, 1969;Fujimoto et al, 1976). Different from the chick, quail PGC did not show GS-I1 reaction at any stages examined, indicating that no glycogen granules were Dresent in the germ cells.…”
Section: Discussionsupporting
confidence: 70%
“…Avian PGCs originate from the epiblast (Eyal-Giladi et al, 1981) and gradually move to the lower layer during the early stages o f primitive streak formation (Sutasurya et al, 1983). They then appear in the hypoblast layer of the germinal crescent region (Swift, 1914;Clawson and Domm, 1969). Subsequently, they enter t h e developing blood vascular syst e m and circulate temporarily throughout the embryo (Swift, 1914;Fujimoto et al, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports focused on it, but whether the numbers of PGCs increase or not from primitive streak stage to seventh somite stage is still uncleared. Clawson and Domm (1969) found there was no obvious increase of PGCs in chick from primitive streak stage to fourth somites period, but obvious increase at the stage of seventh somite. David (1975) found obvious increase of PGCs from primitive streak stage to seventh somites period, in chick and quail.…”
Section: Discussionmentioning
confidence: 74%
“…As for the problem of the nons-ymmetrical distribution of PGCs in the reproduction region, different avian species demonstrated different modes. Fargeix (1969) found the non-symmetricity in duck and Clawson and Domm (1969) also found the same in chicken. However, Pardanaud et al (1987a) found that the distribution of PGCs was highly erratic and varied randomly between the blastodisc.…”
Section: Discussionmentioning
confidence: 81%